PREVALENCE OF ESCHERICHIA COLI AND SALMONELLA SP. IN THE GASTROINTESTINAL TRACT OF LAYING HENS IN JATILUWIH VILLAGE, TABANAN REGENCY, BALI - Laela Rahmatina; Hamong Suharsono; Romy Muhammad Dary Mufa (Buletin Veteriner Udayana, 2025)
Layer poultry farming plays a vital role in ensuring food security by providing a safe, affordable, and high-quality source of animal protein through egg production. However, the industry faces significant challenges, particularly bacterial infections such as Escherichia coli and Salmonella sp., which can impact both poultry productivity and human health. This study aims to detect the presence of Escherichia coli and Salmonella sp. infections in the digestive tracts of deceased layer hens at poultry farms in Jatiluwih Village, Penebel Subdistrict, Tabanan Regency. The research employed an observational method with a descriptive approach, using swab samples taken from the small intestines of chickens that had died within 1–3 hours. Of the 100 samples analyzed, 63% tested positive for Escherichia coli, 2% for Salmonella sp., while 35% were suspected of being infected by other bacteria. These findings indicate a high prevalence of E. coli infection, which poses a potential threat to food safety and increases the risk of zoonotic transmission. Early detection and effective bacterial control measures are therefore essential to maintain farm sustainability and ensure the safety of egg products.